2007
DOI: 10.1111/j.1538-7836.2007.02668.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of inferior vena cava filters in anticoagulated patients

Abstract: Summary.  Background and objectives: The benefit of an inferior vena cava (IVC) filter in addition to standard anticoagulation regimens is unknown. Methods: We examined data for patients who received IVC filters with anticoagulation (AC‐Filter) after an episode of venous thromboembolism (VTE) and compared them with data for those who received anticoagulation only (AC‐Only). Outcome measures were new pulmonary embolism (PE), recurrent deep vein thrombosis (DVT), and mortality at 90 days and at 5 years. Demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…This again suggests that IVCF may not provide any substantial additional benefit for patients who can tolerate anticoagulation. 23 The Cochrane Peripheral Vascular Diseases Group reviewed 2 randomized studies involving 529 patients. 24 The first study involving 129 patients with hip fractures 25 showed a reduction in PE rates in the filter group as compared to the control group (4 of 41 vs 19 of 59, relative risk [RR] 0.3, 95% CI 0.11-0.82).…”
Section: Discussionmentioning
confidence: 99%
“…This again suggests that IVCF may not provide any substantial additional benefit for patients who can tolerate anticoagulation. 23 The Cochrane Peripheral Vascular Diseases Group reviewed 2 randomized studies involving 529 patients. 24 The first study involving 129 patients with hip fractures 25 showed a reduction in PE rates in the filter group as compared to the control group (4 of 41 vs 19 of 59, relative risk [RR] 0.3, 95% CI 0.11-0.82).…”
Section: Discussionmentioning
confidence: 99%
“…The ACCP 2008 antithrombotic therapy of VTE guidelines recommend against the routine use of a vena cava filter in addition to anticoagulation for initial treatment of DVT and PE [7]. Billett et al [28] recently performed a retrospective study that compared clinical outcomes of patients with VTE who were treated with anticoagulation and filter vs. anticoagulation alone. There were no differences in outcome measures of new PE, recurrent DVT or mortality, but patients with a prior history of PE from either group were more likely to have a new PE.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective case-control study Billet et al [58] compared outcomes in 251 patients who received IVC filters in addition to AC (AC-filter) to 1,377 patients on anticoagulation only (AC only). More than 50% of their study population received therapeutic anticoagulation (INR of at least 2) in both the groups for at least 1 year.…”
Section: Combining Anticoagulation and Ivc Filtration In Patients Witmentioning
confidence: 99%